Something left behind: a rare complication of copper-T insertion - Dubey, Kanak; Chawla, Latika; Rajaram, Shalini; Kumari, Om; Bhandari, Janhawi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
This case report presents a unique and intriguing clinical scenario involving an incorrect copper T insertion following a caesarean section. The case presented the importance of training in the right technique for intra-uterine contraceptive device (IUCD) insertions in peripheral health facilities and the potential risks associated with inappropriate procedures. Prompt identification and management of misplaced IUCDs are crucial in minimizing patient discomfort, preventing complications, and optimizing reproductive health outcomes.